PENEGAKAN HUKUM DELIK PENYUAPAN DAN GRATIFIKASI DALAM UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Agil, Marwan; Maryano, Maryano; Kristiawanto, Kristiawanto (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to examine the implementation of bribery and gratuity offenses and analyze the form of law enforcement against bribery and gratuities in corruption cases in Indonesia in the future.  The method used is the normative or doctrinal research method. In this study, the implementation of the bribery and gratuity offense (ius constitutum) applied is Article 5 paragraph (2) jo Article 5 paragraph (1) of Law No.31/1999 as amended by Law No.20/2001 concerning the Eradication of Corruption Crimes (PTPK Law) with the occurrence of simultaneous regulations (concursusu idealis), so that law enforcement both Police Investigators, Prosecutors, and KPK must apply article 12 letter a or b. The results of this study show that in several Court Decisions such as Decision Number 10/PID. SUS-TPK/2021/PT DKI jo Decision Number 234 K/Pid.Sus/2009 jo Decision Number 286/Pid-Sus-TPK/2016/PN SBY, one of the articles that is often charged by prosecutors, namely Article 5 paragraph (2) compared to using Article 12 letter a or b, even though there is a basis for criminal ballasty, namely by using positions and joint regulations so that the right article to be used is Article 12 letter a or b